Fire safety of composites in prefabricated buildings: From fibre reinforced polymer to textile reinforced concrete. (15th April 2020) - Nguyen, Kate T.Q.; Navaratnam, Satheeskumar; Mendis, Priyan; Zhang, Kevin; Barnett, Jonathan; Wang, Hao
Abstract: Fibre reinforced composites (FRCs) have been increasingly used in the prefabricated building (PB) industry owing to its high strength-to-weight ratio, ease of application and flexibility in manufacturing. FRCs can be used in PBs for both structural and non-structural applications. The major hindrance for composite elements in PB is their fire performance. Depending on applications, there will be different requirements for FRCs on the fire resistance and vertical flame spread. There is limited information available to structural and façade engineers/designers on fire safety of FRCs especially for PBs. Therefore, this paper provides the overview on the fire performance FRCs in PBs with a special focus on fibre reinforced polymer and textile reinforced concrete. Highlights: Fire performance of fibre reinforced composites (FRCs) Structural and non-structural application of FRCs in prefabricated building (PB) Basis fire design requirements for PB Potential research studies needed for fire safety of PB with FRCs elements